2020
DOI: 10.18494/sam.2020.2681
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Structure of Computer Numerical Control Grinding Machine Based on Finite Element Method Simulation and Sensor Technology

Abstract: For tool machinery design, the type of machine structure plays an important role in its final machining precision. In the marketplace, structure types change very quickly because of different application purposes and customers' requirements. Moreover, to develop new and good machine structures, designers usually pay too much time and money in the work of trial and error. For a quick response to market needs, machine makers should find time-saving and money-saving ways to optimally design and verify their produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
2
2
1
Order By: Relevance
“…CL = 3091 mm (level 2), CW = 2068.8 mm (level 3), BH = 550 mm (level 1), BW = 2205.5 mm (level 2) (19) As expected, this corresponds to Case 6, which has the smallest δ s among the cases.…”
Section: Optimization Based On Static Rigiditysupporting
confidence: 68%
See 1 more Smart Citation
“…CL = 3091 mm (level 2), CW = 2068.8 mm (level 3), BH = 550 mm (level 1), BW = 2205.5 mm (level 2) (19) As expected, this corresponds to Case 6, which has the smallest δ s among the cases.…”
Section: Optimization Based On Static Rigiditysupporting
confidence: 68%
“…Recently, with the development of highly rigid machine structures, increasing importance has been attached to the dynamic responses of machines. (19,20) In summary, the optimal consideration of both the static and dynamic stiffnesses of the machine structure is a prerequisite for designing a good machine tool.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…Furthermore, a comparison of the results of this study with those of a similar study for the same target machine is made as follows. In the previous study by Wang et al, (28) the target CNC grinding machine based on the optimization of static stiffness exhibited good static behavior with a maximum static deformation of 0.0131 mm, while in this study, it exhibits slightly worse behavior with a maximum static deformation of 0.0143 mm, about 9% larger. In contrast, the optimal target structure in Ref.…”
Section: Optimal Structure Verification and Comparisoncontrasting
confidence: 45%
“…In contrast, the optimal target structure in Ref. 28 showed a dynamic deformation of 0.486 mm at 35.9 Hz (similar to that of Case 1 in this study), while in this study, it exhibited better dynamic stiffness with a maximum deformation of 0.148 mm at 40 Hz, about 30% smaller. Note that under real cutting conditions, only the dynamic stiffness has a major influence on the final precision of cutting for a machine tool.…”
Section: Optimal Structure Verification and Comparisonsupporting
confidence: 43%
“…However, the acceptable measurement results of static stiffness for Case B have shown that our simulation results via FEM are convincing. To further verify the correctness of the calculation and measurement results of our target MDMC, we now compare the static stiffness of our target MDMC with that of a large movingcolumn horizontal machining center machine (HMC), (21) as shown in Table 5. It can be seen that the relative error of the calculated static rigidity between MDMC and HMC is 5.8%, whereas the relative error of the measured static rigidity between them is 8.9%.…”
Section: Comparisonmentioning
confidence: 99%